2002
DOI: 10.1093/chemse/27.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Acuity after Total Laryngectomy

Abstract: The olfactory acuity of 29 patients receiving laryngectomy was prospectively studied. The olfactory acuity was evaluated by Jet Stream Olfactometer (JSO) and Alinamin test preoperatively and at 3, 6 and 12 months postoperatively. The findings of nasal/olfactory mucosae were also observed by rigid endoscope. Based on the results of JSO, the averages of detection/recognition thresholds tended to increase 3 months postoperatively, then the averaged thresholds tended to decrease thereafter. There were significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2
10

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 12 publications
1
28
2
10
Order By: Relevance
“…Although several international studies have described aspects of the assessment and rehabilitation of olfaction in total laryngectomized patients, for decades 9,29,36 , few Brazilian studies have been giving attention to this theme 27,37 . It is necessary to assess and rehabilitate such function, since its alteration causes negative impacts on quality of life, nourishment and even on the patients' safety.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although several international studies have described aspects of the assessment and rehabilitation of olfaction in total laryngectomized patients, for decades 9,29,36 , few Brazilian studies have been giving attention to this theme 27,37 . It is necessary to assess and rehabilitate such function, since its alteration causes negative impacts on quality of life, nourishment and even on the patients' safety.…”
Section: Discussionmentioning
confidence: 99%
“…A study developed with the loss of nasal air flow contributes to olfaction disorders in total laryngectomized patients 9,30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8] Olfactory epithelial damage is also reported to be a consequence of laryngectomy, 1,3,6,7,9 although this is controversial. 10 Much effort has been put into overcoming this problem, 4,5,11 but most attempts have been unsuccessful. 12 In 2000, Hilgers et al reported a nasal airflow-inducing manoeuvre that aimed to solve this problem, and had a noticeable success rate.…”
Section: Introductionmentioning
confidence: 99%